2009
DOI: 10.1510/icvts.2009.202580
|View full text |Cite
|
Sign up to set email alerts
|

The maximum standardized uptake values on positron emission tomography to predict the Noguchi classification and invasiveness in clinical stage IA adenocarcinoma measuring 2 cm or less in size

Abstract: This study investigated whether the standardized uptake value (SUV) of the tumor correlated with the Noguchi classification and tumor invasiveness in patients with clinical stage IA adenocarcinoma < or = 2 cm in size. Fifty-four patients that underwent a curative surgical resection for clinical stage IA adenocarcinoma < or = 2 cm from April 2005 to December 2008 had integrated positron emission tomography (PET)-computed tomography (CT) with 18F-fluorodeoxyglucose (FDG) as part of the preoperative workup. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Several studies in which tumor grading of small adenocarcinoma was found to correlate with radiologic findings obtained with TSCT or FDG-PET have been published (8,9). Takashima et al (8) evaluated various thin-section CT findings to differentiate invasive adenocarcinoma with lepidic growth from adenocarcinoma in situ and suggested that percentage of GGO areas of the lesion on transverse TSCT images were most useful for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in which tumor grading of small adenocarcinoma was found to correlate with radiologic findings obtained with TSCT or FDG-PET have been published (8,9). Takashima et al (8) evaluated various thin-section CT findings to differentiate invasive adenocarcinoma with lepidic growth from adenocarcinoma in situ and suggested that percentage of GGO areas of the lesion on transverse TSCT images were most useful for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Takashima et al (8) evaluated various thin-section CT findings to differentiate invasive adenocarcinoma with lepidic growth from adenocarcinoma in situ and suggested that percentage of GGO areas of the lesion on transverse TSCT images were most useful for this purpose. Maeda et al (9) reported that the use of PET SUV max resulted in discrimination between the two categories with 93% accuracy. Takashima et al (8) further found that the prevalence of coarse spiculation in invasive adenocarcinoma with lepidic growth was statistically significantly greater than that in adenocarcinomas in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Maeda et al (7) analyzed the relationship between PET-CT and tumor subtypes of 54 patients defined by Noguchi et al . (3).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies in which high-resolution CT findings were correlated with the histologic subtypes of peripheral adenocarcinoma of the lung defined by Noguchi et al (5, 6). However, there are only a few reports on the relationship of fluorine 18-fluoro-2-deoxyglucose positron emission tomography CT (F18-FDG PET-CT) with this tumor classification (7, 8). In this study, we investigated if visual assessment and maximum standard uptake values (SUV max ) on PET-CT may correlate with the histology grading of small peripheral adenocarcinoma of the lung.…”
mentioning
confidence: 99%
“…Malignite olasılığı düşük, 8 mm'den kü-çük solid nodül veya subsolid nodül varlığında PET'in duyarlılığı düşer (%47-89) ve yanlış negatif oranı yükselir [3,32,33]. Duyarlılığın dü-şüklüğü, küçük nodüllerin tanınmasında yönte- [33][34][35]. Aslında PET kü-çük, subsolid nodüllerden çok, malign olasılı-ğı yüksek, 10-15 mm'den büyük, kısmi solid TAN'ların değerlendirilmesinde yararlıdır [36].…”
Section: Fonksiyonel Görüntülemeunclassified